Examining Associations of Coping Strategies with Stress, Alcohol, and Substance use among College Athletes: Implications for Improving Athlete Coping - Knettel, Brandon A.; Cherenack, Emily M.; Rougier-Chapman, Conner; Bianchi-Rossi, Courtney (Journal of Intercollegiate Sport, 2023)
Mental health challenges and substance use are common among college athletes, yet few studies have been conducted to understand substance use as a coping strategy. The pressures of collegiate athletics - including commitments to training, travel, and competition - can contribute to maladaptive coping among college athletes, including alcohol and other substance use. An online survey was completed by 188 college athletes competing across NCAA/NJCAA divisions at six institutions in the United States to examine factors associated with substance use coping and whether specific strategies of coping were associated with risk of substance use. Alcohol and drug use were assessed using the CRAFFT Screening Test, NIDA-Modified ASSIST, and Alcohol Use Disorders Identification Test. Coping was assessed with the Coping Orientation to Problems Experienced Inventory, stress was assessed using an adapted Graduate Stress Inventory, athletics-related anxiety was assessed with the Sport Anxiety Scale, and perceived control of stress was assessed using the Perceived Control Questionnaire. Older athletes, men, and those with higher stress were more likely to use substances to cope. Higher behavioral disengagement, higher substance use coping, and lower religious coping were associated with increased likelihood of binge drinking and substance-related risk behaviors. These findings point to the importance of developing targeted interventions aimed at addressing stress and facilitating healthy coping to reduce problematic drinking and substance use among college athletes.